A Psychological Study on Literature and Character Evaluation's Influence - Dina Febriyana Putri; Hanifah Diah Indriyaningrum; Rahma Dita Indriani (International Forum of Researchers and Lecturers, 2024)
This psychological study explores the impact of literature on character assessment. By investigating how literature influences the perception and evaluation of characters, the research delves into the psychological mechanisms underlying readers' interpretations and judgments. Through empirical analysis and theoretical frameworks, the study aims to elucidate the complex relationship between literature and character evaluation, shedding light on its implications for understanding human cognition and behavior.